Effects of Instagram on visitors’ place attachment to the historic city centre in Georgetown, Penang - Meric, Tugce Ertan; Ujang, Norsidah; MacKee, Jamie (Universiti Putra Malaysia, 2023)
Sustaining place identity has become a great challenge today due to the globalization and fast urbanization of cities. Historic city centres are vital cores of place identity because they hold meaning and special memories. However, most revitalization and conservation approaches for historic urban areas focus on physical aspects and undermine the meaning of place and signiﬁcance of people’s attachment to place. Due to the ever-increasing social media usage, people-place bonds have also been transformed irreversibly. This paper examines the effect of Instagram usage on visitors’ place attachment to historic city centres by incorporating destination image, place involvement, and collective memory as mediators in a proposed research model. The data is collected from 41 visitors of Georgetown, Penang in Malaysia. The results’ analysis reveals that Instagram usage has a positive effect on destination image, place involvement and collective memory, which lead to place attachment. Theoretical contribution of the study involves a model that adopts the destination image, place involvement and collective memory concepts testing their effect as on visitors’ place attachment to historic city centres. Second, this study demonstrates the utility of six-dimensional place attachment. Findings also beneﬁt urban practitioners for enhancing place identity in heritage revitalization projects.